A Voyage of Long Term Evolution-Advance (LTE-A): A literature Review - Pandey, Aarti (International Journal of Advanced Science and Technology, 2019)
Future generations has put high demand on use of internet and video services. To fulfill these requirements the prior generations like first, second and third are not up to the mark. To overcome this fourth generation is used which provides much higher peak data rates so that better quality of experience can be given to customers. The objective of this paper is to provide gist to the beginners who are exploring their research carrier in wireless networking at the age when fourth generation technology named as a Long Term Evolution is at peak of its exploration. The paper gives the view of LTE-A, Quality of service (QOS) and how both these terms contribute to design a scheduler for resource allocation. LTE-A architecture, features and its challenges are discussed in the paper. The paper will surely build a sequenced flow in mind of readers to grasp the idea of LTE-A.